2016
DOI: 10.1007/s12195-016-0446-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Enhanced Cellular Uptake and Cytosolic Retention of MK2 Inhibitory Peptide Nano-polyplexes

Abstract: Electrostatic complexation of a cationic MAPKAP kinase 2 inhibitory (MK2i) peptide with the anionic, pH-responsive polymer poly(propylacrylic acid) (PPAA) yields MK2i nano-polyplexes (MK2i-NPs) that significantly increase peptide uptake and intracellular retention. This study focused on elucidating the mechanism of MK2i-NP cellular uptake and intracellular trafficking in vascular smooth muscle cells. Small molecule inhibition of various endocytic pathways showed that MK2i-NP cellular uptake involves both macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 43 publications
(84 reference statements)
2
51
0
Order By: Relevance
“…3739 Our in vitro decoration approach preserved the favorable endogenous composition of EVs as delivery vectors, thus eliminating the need to build artificial endosome-escape strategies into the EV vectors compared to using other synthetic nanovectors for siRNA delivery. 44, 45 …”
Section: Inhibition Of Tumor Growth By Ligand-3wj-displaying Evsmentioning
confidence: 99%
“…3739 Our in vitro decoration approach preserved the favorable endogenous composition of EVs as delivery vectors, thus eliminating the need to build artificial endosome-escape strategies into the EV vectors compared to using other synthetic nanovectors for siRNA delivery. 44, 45 …”
Section: Inhibition Of Tumor Growth By Ligand-3wj-displaying Evsmentioning
confidence: 99%
“…Concentrations. A characteristic feature of damaged endosomes (20)(21)(22)(23)(24)(25)(26) is the presence of cytosolic β-galactosides that are ordinarily found on the luminal side of endolysosomal compartments (27).…”
Section: Cpmps and Cpps Do Not Induce Gal Recruitment At Submicromolarmentioning
confidence: 99%
“…In particular, Gal3 and Gal8 are recruited to damaged Rab7 + and Lamp1 + endosomes that form along the degradative branch of the endocytic pathway (20,31). Previous work has shown that endosomal damage can be detected by monitoring the translocation of eGFP fusions of Gal3 or Gal8 from the cytosol to endosome surfaces (20)(21)(22)(23)(24)(25)(26). However, the effects of CPPs or CPMPs on the extent of Gal-recruitment to potentially damaged endosomes have not previously been studied.…”
Section: Cpmps and Cpps Do Not Induce Gal Recruitment At Submicromolarmentioning
confidence: 99%
“…A characteristic feature of endosomes that have been damaged by invading viruses (29, 30), bacteria-triggered autophagy (31)(32)(33)(34), or endosomolytic nanoparticles (35) is the cytosolic display of β-galactosides linked to proteoglycans that are ordinarily found on the luminal side of endolysosomal compartments (36). Once displayed to the cytosol, β-galactosides recruit cytosolic galectin (Gal) proteins (37,38), such as Gal1, 3, 4, 8, and 9, that share a conserved βgalactoside binding site ( Figure S2A) (39,40).…”
Section: Cpmps and Cpps Do Not Induce Galectin Recruitment At Sub-micmentioning
confidence: 99%
“…Previous work has shown that endosomal damage can be detected by monitoring the translocation of eGFP fusions of Gal3 or Gal8 from the cytosol to endosome surfaces (29-34). Fusions of Gal3 or Gal8 and eGFP have also been used to visualize late endosome damage upon siRNA release from endosomes (40), screen for small molecules that induce lysosomal rupture (41), visualize endosomal leakage induced by osmocytosis and propanebetaine (iTOP) (42), and evaluate cell-permeant peptide-polymer complexes (35). However, the effects of CPPs or CPMPs on the extent of galectin-recruitment to damaged endosomes have not previously been studied.…”
Section: Cpmps and Cpps Do Not Induce Galectin Recruitment At Sub-micmentioning
confidence: 99%